Interaction of Phase Transformations and Plasticity at the Nanoscale: Phase Field Approach. (2015) - Levitas, V.I.; Javanbakht, M.
Abstract: Phase field approach (PFA) to the interaction between phase transformations (PTs) and dislocations is developed at large strains as a nontrivial combination of our recent advanced PFAs to martensitic PTs and dislocation evolution. Finite element method (FEM) simulations are performed to solve the coupled phase-field and elasticity equations and are applied to study of the growth and arrest of martensitic plate for temperature-induced PTs, the evolution of dislocations and high pressure phase in a nanograined material under pressure and shear, and the dislocation inheritance for stress-induced PT.